'Metaphyseal dysplasia without hypotrichosis' can present with late-onset extraskeletal manifestations. Issue 1 (14th August 2019) - Vakkilainen, Svetlana; Costantini, Alice; Taskinen, Mervi; Wartiovaara-Kautto, Ulla; Mäkitie, Outi
Abstract : Background: Metaphyseal dysplasia without hypotrichosis (MDWH) is a rare form of chondrodysplasia with no extraskeletal manifestations. MDWH is caused by RMRP mutations, but it is differentiated from the allelic condition cartilage-hair hypoplasia (CHH), which in addition to chondrodysplasia is characterised by thin hair, immunodeficiency and increased risk of malignancy. The long-term outcome of MDWH remains unknown. Objective: We diagnosed severe agranulocytosis in a subject with RMRP mutations and normal hair. Based on this observation, we hypothesised that MDWH may, similar to CHH, associate with immune deficiency and malignancy. Methods: We collected clinical and laboratory data for a cohort of 80 patients with RMRP mutations followed for over 30 years and analysed outcome data for those with features consistent with MDWH. Results: In our cohort, we identified 10 patients with skeletal but no extraskeletal features during preschool age. Eight of these patients developed malignancy or clinically significant immunodeficiency during follow-up. Two of them died during chemotherapy for malignancy. At the time of the first extraskeletal manifestation, patients were school aged, 20, 43 and 50 years old. Laboratory signs of immunodeficiency (impaired lymphocyte proliferative responses) were demonstrated in four patients before the onset of symptoms. The patient outside this cohort, who had RMRP mutations, skeletal dysplasia, normal hair and severe agranulocytosis at 18 years of age, underwent haematopoietic stem cell transplantation. Conclusions: MDWH can present with severe late-onset extraskeletal manifestations and thus should be reclassified and managed as CHH.